Representation of Emotional Intelligence in a Bilingual Children's Story and Its Implications for Multiliteracy Learning for Beginning Readers - Liza Septa Wilyanti; Sovia Wulandari; Julisah Izar; Helty; Merti Megawaty (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This research aims to describe the representation of emotional intelligence in a bilingual Indonesian–Jambi Malay children’s story and its implications for multiliteracy learning for beginning readers. The object of this research is a children's storybook titled Batu Tuo Si Fosil Kayu by Eko Wahyudi. The research data consists of words, phrases, sentences, dialogues, narratives, and illustrations. The data source is a bilingual Indonesian–Jambi Malay children's storybook titled Batu Tuo Si Fosil Kayu by Eko Wahyudi, published by the Ministry of Primary and Secondary Education in 2024. This research used a descriptive qualitative approach. The data were analyzed using the five components of emotional intelligence, as described by to Daniel Goleman’s theory. The research instrument was the researcher, with data analysis techniques including data classification, analysis, and interpretation, as well as the design of teaching materials for literacy learning. The results indicate that all indicators of emotional intelligence—namely self-awareness, emotional regulation, motivation, empathy, and social skills—are present in the analyzed children’s story. The most dominant indicators are empathy and social skills, reflected through character interactions. Furthermore, this bilingual children’s story features a simple plot, communicative language, and contextual illustrations, making it suitable for beginning readers. Therefore, a bilingual Indonesian–Jambi Malay children’s story has the potential to serve as an alternative, multiliteracies-based instructional material to strengthen the emotional intelligence of beginning readers.